TheMA - Open Access Research Journal for Theatre, Music, Arts. Traduzioni, adattamenti e adozioni. Tradure il teatro del Sei e Settecento oggi, Vol. III/1-2 (Hollitzer, 2024)
TheMA is a peer-reviewed open-access research journal dedicated to the history of performing and visual arts. It is published biannually by HOLLITZER Wissenschaftsverlag in cooperation with Don Juan Archiv Wien, a non-governmental study centre for the history of theatre and culture in general, and Studium Fæsulanum, a non-governmental research centre dedicated primarily to the artistic and intellectual relevance of Central Tuscany around Florence and her Etruscan ‘mother’ Fiesole in the history of culture, the home of the first ‘villa’ of modern times and the birthplace of what we know as ‘opera’. TheMA specializes in the critical and trans-disciplinary historical study of artistic production and reception in various artistic genres including literature, theatre, music, painting, sculpture, and architecture. While Middle, Central and Mediterranean Europe before 1900 is TheMA’s principal area of focus, it welcomes contributions on other regions or periods. The journal’s editors are particularly interested in research that disregards the traditional borders between the various specializations within the Humanities and Social Sciences in favour of a holistic approach to the study of cultural phenomena. TheMA also invites critical contributions themed on regions (such as Europe’s eastern half and adjacent territories in western Asia), which until now have been marginalized in international academic discourse.